FACTOR RELATED TO PUBLIC ANXIETY DURING THE COVID-19 PANDEMIC - Binta Fora Agnesytia; Ani Haryani; Dewi Rahmawati (Journal of Islamic Nursing, 2022)
Abstract The Covid-19 pandemic is a circumstance that can trigger anxiety in the community. Anxiety can be harmful to one's mental health. The aim of this research was to determine the factors that influence public anxiety during the Covid-19 pandemic. This study is descriptive correlational research with a cross sectional approach. A total of 96 respondents were involved from three villages with the characteristics of distant, middle, and close to urban areas. Samples from each village were selected using a purposive sampling technique. Public anxiety was measured using the Coronavirus Anxiety Scale. The relationship between variables was analyzed using the Chi-Square Test. The results showed that during the Covid-19 pandemic, most people experienced anxiety (68.8%). Most of the respondents aged <40 years (68.8%), female (62.5%), junior high school education (35.5%), low economic status (66.7) and varied sources of information (75% ). The factor related to public anxiety during the Covid-19 pandemic in the work area of the Kasemen Health Center was age (p value: 0.0001; OR = 11.2). Factors of gender, education, economic status, and sources of information have no relationship with public anxiety during the Covid-19 pandemic. Keywords: public anxiety, Covid-19 pandemic